3D Tailored Crumpling of Block‐Copolymer Lithography on Chemically Modified Graphene. Issue 8 (14th December 2015) - Kim, Ju Young; Lim, Joonwon; Jin, Hyeong Min; Kim, Bong Hoon; Jeong, Seong‐Jun; Choi, Dong Sung; Li, Dong Jun; Kim, Sang Ouk
Abstract : Novel 3D self‐assembled nanopatterning is presented via tailored crumpling of chemically modified graphene. Block‐copolymer self‐assembly formed on a layer of chemically modified graphene provides highly dense and uniform 2D nanopatterns, and the controlled crumpling of the chemically modified graphene by mechanical instabilities realizes the controlled 3D transformation of the self‐assembled nanopatterns.